Assessing willingness to pay for safe drinking water in Tala union of Satkhiradistrict, Bangladesh - Dey, Nepal C.; Parvez, Mahmood; Saba, Ratnajit; Khan, AS Moniruzzaman; Rahman, Md. Sajidur; Khanam, Roufa; Khan, Md. Reaz Uddin; Barna, Milan K.; Islam, Akramul (© 2016 Published by BRAC University, 2017)
This article was published in the BRAC University Journal [© 2016 Published by BRAC University]